An assessment of the postcranial skeleton of the Paracolobus mutiwa (Primates: Colobinae) specimen KNM-WT 16827 from Lomekwi, West Turkana, Kenya. Issue 156 (July 2021) - Anderson, Monya
Abstract: The postcranium of a large-bodied colobine monkey attributed to Paracolobus mutiwa from the site of Lomekwi, West Turkana, Kenya, is described. The partial skeleton (KNM-WT 16827) was recovered from locality LO 1, dated to 2.58–2.53 Ma, and preserves postcranial elements including fragments of scapula, humerus, proximal ulna, proximal radius, os coxae, proximal femur, astragalus, and calcaneus. KNM-WT 16827 was identified as P. mutiwa based on cranial similarities to the holotype female maxilla (KNM-ER 3843) and the holotype of Paracolobus chemeroni (KNM-BC 3), but is currently the only specimen of this taxon with associated cranial and postcranial elements. The skeleton is morphologically distinct from other large cercopithecid specimens from the Turkana Basin, including several assigned to Cercopithecoides williamsi, Cercopithecoides kimeui, Rhinocolobus turkanaensis, and Theropithecus oswaldi and differs from KNM-BC 3 in the larger cranium and shorter and more robust long bones. KNM-WT 16827 has forelimb and hindlimb features exhibiting a mixture of traits more associated with terrestrial locomotor behavior, including robust humeral deltoid tuberosity, retroflexed humeral medial epicondyle, deep ulnar trochlear notch, relatively short lower iliac height, prominent femoral greater trochanter, asymmetrical astragalar trochlea, and weak digit flexor grooves on the calcaneus. KNM-WT 16827 is also proportionally distinct from KNM-BC 3 and other Turkana Basin specimens attributed to large-bodied taxa such as C. williamsi, C. kimeui, R. turkanaensis, and T. oswaldi in having relatively shorter limbs and smaller tarsals. The traits shared with P. chemeroni and other extinct taxa are either typical for colobines, or likely due to P. mutiwa and P. chemeroni sharing adaptations for terrestrial locomotion relative to extant colobinans. Although a full cranial assessment is needed, based on its postcranial morphology KNM-WT 16827 is distinct from KNM-BC 3, C. williamsi, R. turkanaensis, Theropithecus, and extant colobines, warranting further analyses to better assess the taxonomic assignment of the specimen.